Performance and prospects of the services sector of Barbados - Arthur, Owen ([s.n.] [S.l.], 1995)
Highlights the role played by the hospitality industry; the non-traditional export service industries; the information service sector; the international business and off-shore financial service sector; and, the export services sector in the economy of Barbados. Identifies the key concepts which have helped to guide the development of these sectors in operational terms. Outlines future developments.